Akuntabilitas Pengelolaan Dana Program Mahasiswa Wirausaha (PMW) Universitas Pendidikan Ganesha Didanai Tahun 2019 - Kade Wiwik Antari; Ari Surya Dharmawan (Universitas Pendidikan Ganesha, 2021)
Student’s Entrepreneurship Program is a program for college which aimed for student by providing facilities in the form capital assistance and business assistance so that students are able to build their own businesses. This research aims to reveal the accountability of Student’s Entrepreneurship Program management funds in Undiksha. This research used qualitative aprroach. Data obtained by interviews, observation, and documentation studies, then analyzed through stages namely data reduction, data display, and conslusion drawing. The analyzed aspects are several steps of financial management namely planning step, actuating step, reporting and responsibility step, and controlling step. The result of the research is that management funds of Student’s Entrepreneurship Program, students haven’t yet applied the accountability principle because in reporting step, student still increase the expenditure amount, manipulate sales amount, and create fiction transaction documents.